Correlation Between Diabetic Retinopathy, Depression Level and Quality of Life in Eye Clinic Zainoel Abidin Hospital - Lia Meuthia Zaini; Devia Alfiza Sari; Vera Dewi Mulia; Annisa Meivira Budiman (Majalah Kedokteran Bandung, 2022)
Diabetic retinopathy (DR) is one of the eye disorders caused by complications of diabetes mellitus (DM). Indonesia has a high prevalence of DR (43.1%) compared to other Asia-Pacific countries. Damage and blockage of blood vessels in the retina causes impaired vision, which may lead to a total vision loss. DR requires special treatment, coupled with regular treatment, that is expensive and may result in depression and poor quality of life. This study aimed to determine the association between the degree of diabetic retinopathy with the level of depression and quality of life in people with DR in the eye clinic of Zainoel Abidin General Hospital Banda Aceh. This cross-sectional study was conducted from April 2018 to January 2019. Data were obtained through funduscopy reading, Hamilton Depression Rating Scale (HDRS) questionnaire, and Short-Form Health Survey (SF-36). The subjects of this study were all diabetic retinopathy patients who were sampled using the accidental sampling method. Based on the Spearman correlation analysis, there was a correlation between degree of DR and depression level (p value of 0.004) and quality of life (p value of 0,037). In conclusion, there is a moderate correlation between the degree of DR with depression level and quality of life among DM patients.